2013
DOI: 10.1007/s13730-013-0081-2
|View full text |Cite
|
Sign up to set email alerts
|

AP-VAS 2012 case report: two patients with rheumatoid arthritis suspected of relapsed microscopic polyangiitis after initiation of dialysis

Abstract: We report two patients with rheumatoid arthritis (RA) who were suspected of microscopic polyangiitis during maintenance dialysis. Case 1 was a 52-yearold woman with RA diagnosed at the age of 38 years and treated successfully with gold compounds. At the age of 43 years, she presented with progressive renal dysfunction and abnormal urine sediments, and a renal biopsy revealed crescentic nephritis with advanced glomerular sclerosis. Myeloperoxidase antineutrophil cytoplasmic antibody (MPO-ANCA) was not measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In our center, as well as in the literature, AAV usually occurred after RA in patients with both RA and AAV [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. This may partially be ascribed to the successful inhibition of RA occurrence by intense immunosuppression in the treatment of AAV.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In our center, as well as in the literature, AAV usually occurred after RA in patients with both RA and AAV [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. This may partially be ascribed to the successful inhibition of RA occurrence by intense immunosuppression in the treatment of AAV.…”
Section: Discussionmentioning
confidence: 80%
“…RA is largely an inflammatory disease limited to joints, whereas AAV is a systemic autoimmune disease usually with multi-organ destructive processes and devastating outcomes. It has been reported that AAV can coexist with RA [3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. This coexistence may not be entirely coincidental, as evidenced by facts such as ANCA positivity in 20% of RA patients [25], a positive association between ANCA titer and rapid joint destruction in early RA [26], the presence of myeloperoxidase-ANCA in synovial fluid of RA patients [27], and AAV sharing susceptibility loci with RA [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation